As interfaces do acolhimento dos estudantes egressos da escola itinerante do MST: desafios da Escola Estadual de Ensino Fundamental Ataliba Rodrigues das Chagas - São Gabriel/RS - Fontoura, Mirieli da Silva (2014)
The Itinerant School was an educational proposal consolidated by the Landless Workers Movement (MST) to meet the children and teenagers living in the camps, they usually located on the edge of the road or into the countryside of Rio Grande do Sul the consolidation of this educational institution has generated several ideas about education offered in schools in the rural area, and after countless debates and the creation of specific laws, rural education has become a teaching proposing an educational project from the reality, values, knowledge, culture of their children. With the closing of the Itinerant Schools and the need to implement an education project in the / field, this research presents a general objective: Understand the process of inclusion of children and adolescents coming from Itinerant School and MST settlements - in educational context of State Elementary School Ataliba Rodrigues das Chagas - located in a rural area of the municipality of São Gabriel / RS. Specific objectives are: a) Meet the State Elementary School Ataliba Rodrigues das Chagas - São Gabriel / RS; b) Observe the spaces / times made at the school for professional development regarding new pedagogical demands for the realization of a field school; c) conduct theoretical depth, reflective discussions, share knowledge and exchange experiences individually and collectively with school educators, with a view to inclusion of students coming from the Itinerant School. The methodology used to develop this work is characterized by qualitative approach anchored in the case study, with the aid of the technique of wheels conversations for data collection. During investigation it was realized that the institution still faces major problems related to infrastructure, resources for school meals and educational organization do in order to accomplish a project of the education field. Also examined students MST are socially included, as present with the majority in the school setting, however, in relation to teaching practices, the content available to them, yet are decontextualized from reality that comes.